Restrictive vs Liberal Blood Transfusion for Acute Upper Gastrointestinal Bleeding: Rationale and Protocol for a Cluster Randomized Feasibility Trial - Jairath, Vipul (Grune And Stratton, 2013)
Acute upper gastrointestinal bleeding (AUGIB) is the commonest reason for hospitalization with hemorrhage in the UK and the leading indication for transfusion of red blood cells (RBCs). Observational studies suggest an association between more liberal RBC transfusion and adverse patient outcomes, and a recent randomised trial reported increased further bleeding and mortality with a liberal transfusion policy. TRIGGER (Transfusion in Gastrointestinal Bleeding) is a pragmatic, cluster randomized trial which aims to evaluate the feasibility and safety of implementing a restrictive versus liberal RBC transfusion policy in adult patients admitted with AUGIB. The trial will take place in 6 UK hospitals, and each centre will be randomly allocated to a transfusion policy. Clinicians throughout each hospital will manage all eligible patients according to the transfusion policy for the 6-month trial recruitment period. In the restrictive centers, patients become eligible for RBC transfusion when their hemoglobin is < 8 g/dL. In the liberal centers patients become eligible for transfusion once their hemoglobin is < 10 g/dL. All clinicians will have the discretion to transfuse outside of the policy but will be asked to document the reasons for doing so. Feasibility outcome measures include protocol adherence, recruitment rate, and evidence of selection bias. Clinical outcome measures include further bleeding, mortality, thromboembolic events, and infections. Quality of life will be measured using the EuroQol EQ-5D at day 28, and the costs associated with hospitalization for AUGIB in the UK will be estimated. Consent will be sought from participants or their representatives according to patient capacity for use of routine hospital data and day 28 follow up. The study has ethical approval for conduct in England and Scotland. Results will be analysed according to a pre-defined statistical analysis plan and disseminated in peer reviewed publications to relevant stakeholders. The results of this study will inform the feasibility and design of a phase III randomized trial.